Cause of death in patients with tuberculosis: A study based on epidemiological and autopsy records of Western Norway 1931-47 - Syeda Mariam Riaz; Lisbet Sviland; Kurt Hanevik; Tehmina Mustafa (Elsevier, 2024)
Background: Without treatment, nearly 50 % of tuberculosis (TB) patients die. World Health Organization's definition of TB deaths does not take into consideration whether the cause of death was TB or other non-TB co-morbid conditions. We aimed to improve our knowledge of the causes of death in patients with TB. Methods: Single-center retrospective study conducted at Gade Institute of Pathology, Haukeland University Hospital, Bergen, Norway. Autopsy data of 269 patients with TB was collected from autopsy journals, and epidemiological data was collected from Norwegian Official Statistics books for period 1931-1947. Results: Of all TB deaths reported in epidemiological reports, pulmonary TB accounted for 81 % and extrapulmonary TB for 19 %. However, in autopsy records, only 21 % of cases with active pulmonary TB died because of TB. Extrapulmonary involvement was significantly associated with higher mortality (OR EPTB as compared to PTB; 3.27, CI 1.91 - 5.61) and constituted 79 % of deaths attributable to TB. A significant burden of extrapulmonary TB was found in autopsy records (63 %), while in epidemiological records, only 4 % of cases were reported. Conclusions: Extrapulmonary involvement was a predictor of mortality due to TB in hospitalized TB patients. The contribution of extrapulmonary TB to TB mortality seems to be underestimated because extrapulmonary TB largely remains underdiagnosed and underreported in epidemiological data.